How to know a person [compact disc, unabridged] - Brooks, David, 1961- (Random House Audio, 2023)
Driven by his trademark sense of curiosity, Brooks draws from the fields of psychology and neuroscience, and from the worlds of theatre, history, and education, to present a welcoming, hopeful, integrated approach to human connection. He helps listeners become more understanding and considerate towards others, and find the joy that comes from being seen. Along the way he offers a possible remedy for a society that is riven by fragmentation, hostility, and misperception. The act of seeing another person, Brooks argues, is a profoundly creative act: How can we look somebody in the eye and see something large in them, and in turn, see something larger in ourselves?